A collaborative approach to the implementation of a structured clinical handover tool (iSoBAR), within a hospital setting in metropolitan Western Australian: A mixed methods study. (November 2018) - Beament, Tania; Ewens, Beverley; Wilcox, Sarah; Reid, Gill
Abstract: The aim of this study was to determine the effectiveness of an education intervention for the implementation of the clinical handover tool iSoBAR, in an acute setting. A quantitative, descriptive survey design, using pre and post survey data before and after the implementation of an education intervention was used. Twenty nine nurses, doctors and allied health personnel employed at the study site participated in the study. The educational intervention consisted of an electronic presentation plus simulated video recorded exemplars of clinical handover. Outcome measures were the efficacy of the education intervention on the confidence of practitioners using the iSoBAR handover tool. Participants' understanding of the iSoBAR tool using Mann-Whitney U test was 2.54 pre-intervention and 4.32 post-intervention. Confidence in using the tool also increased post educational intervention from 2.7 (pre-intervention) to 4.07 (post-intervention). Focus groups identified several factors relating to the implementation of iSoBAR, creating two dominant themes: challenges concerning patient factors and change management processes and systems. Opportunities were identified: Practice enhancement, patient centred care, professional practice, and grassroots initiatives. The use of an interprofessional educational program increased the confidence and understanding of a range of health care practitioners when using the clinical handover tool iSoBAR.